Factors associated with hookah use initiation among adolescents - Caroline C. Reveles; Neuber J. Segri; Clovis Botelho (Brazilian Society of Pediatrics, 2013)
Objective: to determine the prevalence and to analyze factors associated with hookah use initiation among adolescents. Methods: this was a cross-sectional study, in which questionnaires were collected from 495 students attending public and private schools of the urban area of the city of Várzea Grande, in the state of Mato Grosso, Brazil. Data were analyzed through descriptive, bivariate, and multiple Poisson regression analyses. Results: a total of 19.7% students had tried a hookah. The use of hookah was associated with the final period of adolescence [PR = 6.54 (2.79, 15.32)]; enrollment in private schools [PR = 2.23 (1.73, 2.88)]; and presence of work activities [PR = 1.80 (1.17, 2.78)]. Conclusion: the proportion of adolescents that had tried a hookah was high. The influence of age, work activities, and class period on smoking initiation using the hookah was observed. Preventive measures encompassing all forms of tobacco smoking should be targeted at adolescents in the school environment, aiming at tobacco use control.